Southeast Asian seas : (McGraw-Hill, 1981)
The book was initially conceived in response to the Law of the Sea Conferrence with the expectation that its conclution would be imminent. Apart from the desire to follow the various vital issues being egotiated, the emerging consensus on them, and the develop-ments arising therefrom from the standpoint of Southeast Asia, there is also a need to bring together basic information setting out the status and trends, national policies, and current concerns on a range of topics aimed at policy-markets, scholars, and those concerned with one or more aspects of the region's seas.